2018
DOI: 10.1002/jcp.27642
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐140‐5p targeting tumor necrosis factor‐α prevents pulmonary arterial hypertension

Abstract: Background Pulmonary arterial hypertension (PAH) is characterized by the apoptosis resistance and hyperproliferation of pulmonary artery smooth muscle cells (PASMCs). Its pathogenesis has not been revealed. Here, we carried out experiments to investigate the functions of miR‐140‐5p and tumor necrosis factor‐α (TNF‐α). Methods We selected GSE703 from Gene Expression Omnibus (GEO) Database to conduct microarray analysis using R software and Gene Set Enrichment Analysis (GSEA). Combing bioinformatics results, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 47 publications
2
20
0
Order By: Relevance
“…Downregulation of miR-140-5p and upregulation of TNF-α (tumor necrosis factor-α) may induce pathological events in PAHT. 70…”
Section: Mirnas and Hypertensionmentioning
confidence: 99%
“…Downregulation of miR-140-5p and upregulation of TNF-α (tumor necrosis factor-α) may induce pathological events in PAHT. 70…”
Section: Mirnas and Hypertensionmentioning
confidence: 99%
“…MiR-140-5p has been found to be an immune response inhibitor in patients with acute lung injury, osteoarthritis and pulmonary arterial hypertension. [36][37][38] It is reported that miR-140-5p directly target TNF-α and repressed its expression in pulmonary artery smooth muscle cells. 36 In the present study, we confirmed that miR-140-5p also repressed TNF-α in trophoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…At the conclusion of the experiments, the tumors were harvested and stained with hematoxylin-eosin(HE) to discern the histopathological response and evaluate the tumors' morphology. HE staining was conducted according to routine protocols [17]. Brie y, after depara nization and rehydration, 5 μm longitudinal sections were stained with hematoxylin solution for 5 min followed by 5 dips in 1% acid ethanol (1% HCl in 70% ethanol) and then rinsed in distilled water.…”
Section: He Stainingmentioning
confidence: 99%